Motivierende Lernzugänge als Ausgangspunkt der Professionalisierung angehender Lehrer_innen - Caruso, Carina; Adammek, Christine; Bonanati, Sabrina; Wiescholek, Sybille (Herausforderung Lehrer*innenbildung - Zeitschrift Zur Konzeption, Gestaltung Und Diskussion)
Im Artikel werden drei verschiedene Lernzugänge (kom-petenzorientiertes, ästhetisches und biographisches Lernen) vorgestellt und aus theoretischer Perspektive deren motivierender Gehalt für selbstreguliertes Lernen in Praxisphasen des Lehramtsstudiumsherausgearbeitet. Als theoretische Grund-lage dient die Selbstbestimmungstheorie als zentrale motivationale Theorie zur Erklärung selbstbestimmten Handelns.
Keywords: ästhetische Forschung; Biographiearbeit; Praxissemester; Professionalisierung; selbstreguliertes Lernen; Motivation / aesthetic research; biographical work; long-term internship; profes-sionalization; self-regulated learning; motivation

Informationskompetenz durch E-Learning? Durch Lernvideos nach Literatur suchen - Hahn, Charlotte Anna (die hochschullehre)
The aim of this study was to find out whether teaching how to search for literature would be more beneficial to students and teachers if done online through short videos rather than in person during course time. To find out whether online videos are more beneficial, two courses were asked to fill in questionnaires, one at the beginning and one at the end of the semester. One of the courses received the input online via videos and were given an exercise to put the newly learned skills to use, the other course served as a control group and learned how to search for literature during the course. The results show that while the difference between the two groups is not significant, the videos can still be regarded as being more beneficial than teaching the necessary skills during course time.
Keywords: E-Learning; information competence; literature; library; research

Deep Learning as a Competitive Feature-Free Approach for Automated Algorithm Selection on the Traveling Salesperson Problem - Seiler, Moritz; Pohl, Janina; Bossek, Jakob; Kerschke, Pascal; Trautmann, Heike (Parallel Problem Solving from Nature (PPSN XVI))
In this work we focus on the well-known Euclidean Traveling Salesperson Problem (TSP) and two highly competitive inexact heuristic TSP solvers, EAX and LKH, in the context of per-instance algorithm selection (AS). We evolve instances with nodes where the solvers show strongly different performance profiles. These instances serve as a basis for an exploratory study on the identification of well-discriminating problem characteristics (features). Our results in a nutshell: we show that even though (1) promising features exist, (2) these are in line with previous results from the literature, and (3) models trained with these features are more accurate than models adopting sophisticated feature selection methods, the advantage is not close to the virtual best solver in terms of penalized average runtime and so is the performance gain over the single best solver. However, we show that a feature-free deep neural network based approach solely based on visual representation of the instances already matches classical AS model results and thus shows huge potential for future studies.
Keywords: Automated algorithm selection; Deep learning; Feature-based approaches; Traveling Salesperson Problem

Squaring the circle: Business model teaching in large classroom settings - Szopinski, Daniel (Journal of Business Models)
Business model innovation is typically taught in small seminars at universities. Teaching this intrinsically task-oriented subject to a large number of students is a challenge. In this paper we address this challenge by proposing an experiential and interactive approach to teaching business models in a large classroom setting.
Keywords: Business model teaching; peer assessment; experiential learning

A Hypothetical Learning Trajectory for the Learning of the Rules for Manipulating Integers - Schumacher, Jan; Rezat, Sebastian (Proceedings of the Eleventh Congress of the European Society for Research in Mathematics Education (CERME11, February 6 – 10, 2019))
In this paper, we first outline a Hypothetical Learning Trajectory (HLT), which aims at a formal understanding of the rules for manipulating integers. The HLT is based on task formats, which promote algebraic thinking in terms of generalizing rules from the analysis of patterns and should be familiar to students from their mathematics education experiences in elementary school. Second, we analyze two students' actual learning process based on Peircean semiotics. The analysis shows that the actual learning process diverges from the hypothesized learning process in that the students do not relate the different levels of the diagrams in a way that allows them to extrapolate the rule for the subtraction of negative numbers. Based on this finding, we point out consequences for the design of the tasks.
Keywords: diagrammatic reasoning; hypothetical learning trajectory; induction extrapolatory method; integers; negative numbers; permanence principle; semiotics

Deep reinforcement learning for scheduling in large-scale networked control systems - Redder, Adrian; Ramaswamy, Arunselvan; Quevedo, Daniel (Proceedings of the 8th IFAC Workshop on Distributed Estimation and Control in Networked Systems)
This work considers the problem of control and resource allocation in networked systems. To this end, we present DIRA a Deep reinforcement learning based Iterative Resource Allocation algorithm, which is scalable and control-aware. Our algorithm is tailored towards large-scale problems where control and scheduling need to act jointly to optimize performance. DIRA can be used to schedule general time-domain optimization based controllers. In the present work, we focus on control designs based on suitably adapted linear quadratic regulators. We apply our algorithm to networked systems with correlated fading communication channels. Our simulations show that DIRA scales well to large scheduling problems.
Keywords: Networked control systems; deep reinforcement learning; large-scale systems; resource scheduling; stochastic control

Understanding Artificial Intelligence – A Project for the Development of Comprehensive Teaching Material - Schlichtig, Michael; Opel, Simone Anna; Budde, Lea; Schulte, Carsten (ISSEP 2019 - 12th International conference on informatics in schools: Situation, evaluation and perspectives, Local Proceedings)
Artificial intelligence (AI) has the potential for far-reaching – in our opinion – irreversible changes. They range from effects on the individual and society to new societal and social issues. The question arises as to how students can learn the basic functioning of AI systems, what areas of life and society are affected by these and – most important – how their own lives are affected by these changes. Therefore, we are developing and evaluating school materials for the German ”Science Year AI”. It can be used for students of all school types from the seventh grade upwards and will be distributed to about 2000 schools in autumn with the support of the Federal Ministry of Education and Research. The material deals with the following aspects of AI: Discussing everyday experiences with AI, how does machine learning work, historical development of AI concepts, difference between man and machine, future distribution of roles between man and machine, in which AI world do we want to live and how much AI would we like to have in our lives. Through an accompanying evaluation, high quality of the technical content and didactic preparation is achieved in order to guarantee the long-term applicability in the teaching context in the different age groups and school types. In this paper, we describe the current state of the material development, the challenges arising, and the results of tests with different classes to date. We also present first ideas for evaluating the results.
Keywords: Artificial Intelligence; Machine Learning; Teaching Material; Societal Aspects; Ethics. Social Aspects; Science Year; Simulation Game

OpenML: An R Package to Connect to the Machine Learning Platform OpenML - Casalicchio, Giuseppe; Bossek, Jakob; Lang, Michel; Kirchhoff, Dominik; Kerschke, Pascal; Hofner, Benjamin; Seibold, Heidi; Vanschoren, Joaquin; Bischl, Bernd (Computational Statistics)
OpenML is an online machine learning platform where researchers can easily share data, machine learning tasks and experiments as well as organize them online to work and collaborate more efficiently. In this paper, we present an R package to interface with the OpenML platform and illustrate its usage in combination with the machine learning R package mlr (Bischl et al. J Mach Learn Res 17(170):1—5, 2016). We show how the OpenML package allows R users to easily search, download and upload data sets and machine learning tasks. Furthermore, we also show how to upload results of experiments, share them with others and download results from other users. Beyond ensuring reproducibility of results, the OpenML platform automates much of the drudge work, speeds up research, facilitates collaboration and increases the users’ visibility online.
Keywords: Databases; Machine learning; R; Reproducible research

Wissensmanagement unter Bedingungen von Arbeit 4.0 - Harteis, Christian; Fischer, Christoph (Handbuch Gestaltung digitaler und vernetzter Arbeitswelten)
Keywords: i40; learning culture

Digitalisation of Work: Between Affordances and Constraints for Learning at Work - Fischer, Christoph; Goller, Michael; Brinkmann, Lorraine; Harteis, Christian (Digital Workplace Learning)
Keywords: i40; learning culture

ML-Plan for Unlimited-Length Machine Learning Pipelines - Wever, Marcel Dominik; Mohr, Felix; Hüllermeier, Eyke (ICML 2018 AutoML Workshop)
In automated machine learning (AutoML), the process of engineering machine learning applications with respect to a specific problem is (partially) automated. Various AutoML tools have already been introduced to provide out-of-the-box machine learning functionality. More specifically, by selecting machine learning algorithms and optimizing their hyperparameters, these tools produce a machine learning pipeline tailored to the problem at hand. Except for TPOT, all of these tools restrict the maximum number of processing steps of such a pipeline. However, as TPOT follows an evolutionary approach, it suffers from performance issues when dealing with larger datasets. In this paper, we present an alternative approach leveraging a hierarchical planning to configure machine learning pipelines that are unlimited in length. We evaluate our approach and find its performance to be competitive with other AutoML tools, including TPOT.
Keywords: automated machine learning; complex pipelines; hierarchical planning

Improving Classifiers for Semantic Annotation of Software Requirements with Elaborate Syntactic Structure - Kim, Yeongsu; Lee, Seungwoo; Dollmann, Markus; Geierhos, Michaela (International Journal of Advanced Science and Technology)
A user generally writes software requirements in ambiguous and incomplete form by using natural language; therefore, a software developer may have difficulty in clearly understanding what the meanings are. To solve this problem with automation, we propose a classifier for semantic annotation with manually pre-defined semantic categories. To improve our classifier, we carefully designed syntactic features extracted by constituency and dependency parsers. Even with a small dataset and a large number of classes, our proposed classifier records an accuracy of 0.75, which outperforms the previous model, REaCT.
Keywords: Software Engineering; Natural Language Processing; Semantic Annotation; Machine Learning; Feature Engineering; Syntactic Structure

Information Security Investments: An Exploratory Multiple Case Study on Decision-Making, Evaluation and Learning - Weishäupl, Eva; Yasasin, Emrah; Schryen, Guido (Computers & Security)
The need to protect resources against attackers is reflected by huge information security investments of firms worldwide. In the presence of budget constraints and a diverse set of assets to protect, organizations have to decide in which IT security measures to invest, how to evaluate those investment decisions, and how to learn from past decisions to optimize future security investment actions. While the academic literature has provided valuable insights into these issues, there is a lack of empirical contributions. To address this lack, we conduct a theory-based exploratory multiple case study. Our case study reveals that (1) firms? investments in information security are largely driven by external environmental and industry-related factors, (2) firms do not implement standardized decision processes, (3) the security process is perceived to impact the business process in a disturbing way, (4) both the implementation of evaluation processes and the application of metrics are hardly existent and (5) learning activities mainly occur at an ad-hoc basis.
Keywords: Information Security Investments; Multiple Case Study; Organizations; Single Loop Learning; Double Loop Learning

Reciprocal effects between self-concept of ability and performance: A longitudinal study of children with learning disabilities in inclusive versus exclusive elementary education - Gorges, Julia; Neumann, Phillip; Wild, Elke; Stranghöner, Daniela; Lütje-Klose, Birgit (Learning and Individual Differences)
Ample empirical research from regular school settings documents reciprocal effects between academic performance and academic self-concept of ability (ASC), supporting what is known as a reciprocal effects model (REM). The present article investigates a REM in the domain of reading performance in a sample of elementary students with special educational needs in learning (SEN-L) who received special educational support in exclusive versus inclusive settings (N = 446). In exclusive settings, SEN-L students attend special schools and are completely separated from regular students. By contrast, SEN-L students in inclusive settings attend regular schools and are educated in classes with regular students. In both settings, SEN-L students are not graded and taught based on individual learning goals, which may affect reciprocal effects between ASC and reading performance. In addition, given that special education for SEN-L students relies heavily on individual reference standards to evaluate performance, we tested individual performance growth of SEN-L students as a predictor of ASC. Analyses of a longitudinal dataset across 3rd and 4th grade revealed some cross-lagged effects and an effect of performance growth on ASC in exclusive settings in particular. The discussion focuses on the role of individualized instruction, grades, peer groups, and individual versus social reference standards for reciprocal effects between ASC and performance as well as practical implications.
Keywords: BiLieF; Special educational needs; Learning disability; Academic selfconcept of ability; Reciprocal effects model; Inclusive education

Leveraging TSP Solver Complementarity through Machine Learning - Kerschke, Pascal; Kotthoff, Lars; Bossek, Jakob; Hoos, Holger H.; Trautmann, Heike (Evolutionary Computation)
The Travelling Salesperson Problem (TSP) is one of the best-studied NP-hard problems. Over the years, many different solution approaches and solvers have been developed. For the first time, we directly compare five state-of-the-art inexact solvers— namely, LKH, EAX, restart variants of those, and MAOS— on a large set of well-known benchmark instances and demonstrate complementary performance, in that different instances may be solved most effectively by different algorithms. We leverage this complementarity to build an algorithm selector, which selects the best TSP solver on a per-instance basis and thus achieves significantly improved performance compared to the single best solver, representing an advance in the state of the art in solving the Euclidean TSP. Our in-depth analysis of the selectors provides insight into what drives this performance improvement.
Keywords: automated algorithm selection; machine learning.; performance modeling; Travelling Salesperson Problem

Experiential or Self-Regulated Learning: A Critical Reflection of Entrepreneurial Learning Processes - Fust, Alexander Paul; Jenert, Tobias; Winkler, Christoph (Entrepreneurship Research Journal)
Research on entrepreneurial learning highlights the importance of experience and prior knowledge to entrepreneurial success. However, a conundrum remains and we are still seeking answers as to why some novice entrepreneurs learn successfully from their experiences and succeed, while some experienced entrepreneurs fail with their ventures. In order to advance the discussion about the role of experience during entrepreneurial learning, our critical reflection aims to (1) highlight some of the shortcomings of experiential learning theory (ELT) and (2) illustrate how alternative theoretical perspectives have the potential to advance our conceptual understanding of entrepreneurial learning processes. We argue for an explanation of entrepreneurial learning as a dynamic and self-regulated process that relies on planning, monitoring, and self-reflection.
Keywords: entrepreneurial learning; experiential learning; self-regulated learning

Human agency at work: An active approach towards expertise development - Goller, Michael
Michael Goller gives a structured overview of the current discourses of human agency in relation to professional learning and development. Based on this discussion, the author develops a theoretical framework including human agency as an individual feature (i. e., a disposition) as well as a set of self-initiated and goal-directed behaviours that are assumed to affect employees’ learning and development (e. g., crafting of new work experiences). He then further specifies this theoretical framework and investigates it empirically in the domain of geriatric care nursing. Based on the findings of the three empirical studies conducted, the author discusses the relevance of human agency for the development of professional expertise of geriatric care nurses. The work received the American Educational Research Association (AERA) Workplace Learning SIG 2017 Dissertation of the Year Award.
Keywords: Workplace learning; Agency; Expertise

A configuration-based recommender system for supporting e-commerce decisions - Scholz, Michael; Dorner, Verena; Schryen, Guido; Benlian, Alexander (European Journal of Operational Research)
Multi-attribute value theory (MAVT)-based recommender systems have been proposed for dealing with issues of existing recommender systems, such as the cold-start problem and changing preferences. However, as we argue in this paper, existing MAVT-based methods for measuring attribute importance weights do not fit the shopping tasks for which recommender systems are typically used. These methods assume well-trained decision makers who are willing to invest time and cognitive effort, and who are familiar with the attributes describing the available alternatives and the ranges of these attribute levels. Yet, recommender systems are most often used by consumers who are usually not familiar with the available attributes and ranges and who wish to save time and effort. Against this background, we develop a new method, based on a product configuration process, which is tailored to the characteristics of these particular decision makers. We empirically compare our method to SWING, ranking-based conjoint analysis and TRADEOFF in a between-subjects laboratory experiment with 153 participants. Results indicate that our proposed method performs better than TRADEOFF and CONJOINT and at least as well as SWING in terms of recommendation accuracy, better than SWING and TRADEOFF and at least as well as CONJOINT in terms of cognitive load, and that participants were faster with our method than with any other method. We conclude that our method is a promising option to help support consumers' decision processes in e-commerce shopping tasks.
Keywords: E-Commerce; Recommender System; Attribute Weights; Configuration System; Decision Support

Semantic Annotation of Software Requirements with Language Frame - Kim, Yeong-Su; Lee, Seung-Woo; Dollmann, Markus; Geierhos, Michaela (International Journal of Software Engineering for Smart Device)
An end user generally writes down software requirements in ambiguous expressions using natural language; hence, a software developer attuned to programming language finds it difficult to understand th meaning of the requirements. To solve this problem we define semantic categories for disambiguation and classify/annotate the requirement into the categories by using machine-learning models. We extensively use a language frame closely related to such categories for designing features to overcome the problem of insufficient training data compare to the large number of classes. Our proposed model obtained a micro-average F1-score of 0.75, outperforming the previous model, REaCT.
Keywords: Natural Language Processing; Semantic Annotation; Machine Learning

The Multifaceted Nature of Agency and Professional Learning - Paloniemi, Susanna; Goller, Michael (Agency at work: An agentic perspective on professional learning and development)
The present volume has aimed to cover a broad range of approaches to agency at work, exploring its relationship with professional learning and development. Thus, the chapters included in this book have discussed the role of agency in learning and development, considering a variety of working life contexts and applying both conceptual and empirical perspectives. This final chapter provides an overview of both the conceptual approaches and the empirical implementations. We see the perspectives as complementary. From the content of the book, we discern the phenomena as falling on two main dimensions, clustering at opposite ends of these dimensions. Thus, the following contrasts are evidenced: (a) agency understood as a personal capacity, vs. agency as behaviour, and (b) agency as an individual phenomenon, vs. agency as a collective phenomenon. All the chapters emphasise that agency is needed for learning and development. However, they differ in how they view the relationships between the concepts. They also exhibit differences in the empirical decisions taken and the research strategies chosen. In this concluding chapter, we discuss the main similarities and differences emerging from the chapters. We also highlight avenues for future research on agency and its relationship with professional learning.
Keywords: Agency; Workplace learning; Professional development

Listening to learners’ voices: Qualitative aspects of pronunciation learning during study abroad - Müller, Mareike (Journal of Second Language Pronunciation)
This article investigates learners’ perceptions on pronunciation learning in study-abroad contexts from a qualitative perspective. While previous research focused mainly on quantitative measurements of pronunciation gains with mixed results, this study takes a more learner-centered approach and examines the impact of socio-psychological factors on learning foreign pronunciation, which appears to be a highly individual and at times conflict-prone process with which sojourners are confronted. The study draws on the cases of five Canadian students who studied abroad at German universities for one or two semesters. The data collection involved a learning history questionnaire; semi-structured interviews pre-, mid-, and post-sojourn; and bi-weekly e-journals. The data was analyzed and interpreted within the framework of narrative analysis. The results show how sojourners’ beliefs about the importance of pronunciation, community participation, identity-related challenges, and obstacles to pronunciation learning influence and help explain individually different learning behaviors and results.
Keywords: pronunciation learning; study abroad; qualitative approach; narrative analysis; learner beliefs; socio-psychological learning factors

Embodied Language Learning and Cognitive Bootstrapping: Methods and Design Principles - Lyon, Caroline; Nehaniv, Chrystopher L.; Saunders, Joe; Belpaeme, Tony; Bisio, Ambra; Fischer, Kerstin; Forster, Frank; Lehmann, Hagen; Metta, Giorgio; Mohan, Vishwanathan; Morse, Anthony; Nolfi, Stefano; et al. (International Journal of Advanced Robotic Systems)
Co-development of action, conceptualization and social interaction mutually scaffold and support each other within a virtuous feedback cycle in the development of human language in children. Within this framework, the purpose of this article is to bring together diverse but complementary accounts of research methods that jointly contribute to our understanding of cognitive development and in particular, language acquisition in robots. Thus, we include research pertaining to developmental robotics, cognitive science, psychology, linguistics and neuroscience, as well as practical computer science and engineering. The different studies are not at this stage all connected into a cohesive whole; rather, they are presented to illuminate the need for multiple different approaches that complement each other in the pursuit of understanding cognitive development in robots. Extensive experiments involving the humanoid robot iCub are reported, while human learning relevant to developmental robotics has also contributed useful results. Disparate approaches are brought together via common underlying design principles. Without claiming to model human language acquisition directly, we are nonetheless inspired by analogous development in humans and consequently, our investigations include the parallel co-development of action, conceptualization and social interaction. Though these different approaches need to ultimately be integrated into a coherent, unified body of knowledge, progress is currently also being made by pursuing individual methods.
Keywords: Robot Language; Human Robot Interaction; HRI; Developmental Robotics; Cognitive Bootstrapping; Statistical Learning

An Alternative to Mapping a Word onto a Concept in Language Acquisition: Pragmatic Frames - Rohlfing, Katharina; Wrede, Britta; Vollmer, Anna-Lisa; Oudeyer, Pierre-Yves (FRONTIERS IN PSYCHOLOGY)
The classic mapping metaphor posits that children learn a word by mapping it onto a concept of an object or event. However, we believe that a mapping metaphor cannot account for word learning, because even though children focus attention on objects, they do not necessarily remember the connection between the word and the referent unless it is framed pragmatically, that is, within a task. Our theoretical paper proposes an alternative mechanism for word learning. Our main premise is that word learning occurs as children accomplish a goal in cooperation with a partner. We follow Bruner's (1983) idea and further specify pragmatic frames as the learning units that drive language acquisition and cognitive development. These units consist of a sequence of actions and verbal behaviors that are co-constructed with a partner to achieve a joint goal. We elaborate on this alternative, offer some initial parametrizations of the concept, and embed it in current language learning approaches.
Keywords: language acquisition; pragmatics; infants' social learning; frames; learning and memory; developmental robotics

Spielend Lehrer/in werden: problembasiertes Lernen mit virtuellen Schülerinnen/Schülern. - Praetorius, Saskia; Al-Kabbani, Daniel; Bohndick, Carla; Hilkenmeier, Johanna; König, Sebastian T.; Müsche, Hannah S.; Sommer, Sabrina; Klingsieck, Katrin B. (Zeitschrift für Hochschulentwicklung)
Über das Lehramtsstudium sollen Studierende unter anderem dazu befähigt werden, die Leistung ihrer Schüler/innenzu bewerten. Dazu müssen sie Einflussfaktoren auf Schulleistung kennen und diese richtig diagnostizieren und fördern können. Mit diesem Beitrag wird eine game-und E-Learning-gestützte Lernumgebung vorgestellt, in der Studierende –anders als in vielen inputorientierten Seminarkonzepten –in einem virtuellen Klassenzimmer an realitätsnahen Fällen lernen,problembasiert zu diagnostizieren und zu fördern. Über denEinsatz der Lernumgebung in der Lehre wird berichtet, erste Rückmeldungen von Lehrenden und Studierenden werden erläutert und weitere Planungsschritte dargestellt.
Keywords: E-Learning; digitale Medien; problembasiertes Lernen; Lehrerbildung; Diagnostik

Learning Boolean Specifications - Bubeck, Uwe; Kleine Büning, Hans (Artificial Intelligence)
In this paper we consider an extended variant of query learning where the hidden concept is embedded in some Boolean circuit. This additional processing layer modifies query arguments and answers by fixed transformation functions which are known to the learner. For this scenario, we provide a characterization of the solution space and an ordering on it. We give a compact representation of the minimal and maximal solutions as quantified Boolean formulas and we adapt the original algorithms for exact learning of specific classes of propositional formulas.
Keywords: Query learning; Propositional logic

Die Bedeutung subjektiver Sichtweisen für die Implementierung betrieblicher Lernkultur - Fischer, Christoph; Harteis, Christian (Informelles Lernen, Annäherungen - Problemlagen - Forschungsbefunde)
Keywords: Epistemische Überzeugungen; learning culture

The Value of Self-Service: Long-Term Effects of Technology-Based Self-Service Usage on Customer Retention. - Scherer, Anne; Wünderlich, Nancy; Von Wangenheim, Florian (MIS Quarterly)
Advancements in information technology have changed the way customers experience a service encounter and their relationship with service providers. Especially technology-based self-service channels have found their way into the 21st century service economy. While research embraces these channels for their cost-efficiency, it has not examined whether a shift from personal to self-service affects customer–firm relationships. Drawing from the service-dominant logic and its central concept of value-in-context, we discuss customers’ value creation in self-service and personal service channels and examine the long-term impact of these channels on customer retention. Using longitudinal customer data, we investigate how the ratio of self-service versus personal service use influences customer defection over time. Our findings suggest that the ratio of self-service to personal service used affects customer defection in a U-shaped manner, with intermediate levels of both self-service and personal service use being associated with the lowest likelihood of defection. We also find that this effect mitigates over time. We conclude that firms should not shift customers toward self-service channels completely, especially not at the beginning of a relationship. Our study underlines the importance of understanding when and how self-service technologies create valuable customer experiences and stresses the notion of actively managing customers’ cocreation of value.
Keywords: customer defection; customer retention; e-service; longitudinal; Self-service; value-in-context

The self-fulfilling prophecy of fear of academic failure - Brahm, Taiga; Jenert, Tobias; Wagner, Dietrich
Academic success in Higher Education is influenced by a number of different factors. This paper tackles the question if the individual levels of motivation, anxiety, enjoyment and self-efficacy, measured immediately before entering university, influence the probability of academic success. Former studies have shown an influence of the high school grade, the learning environment and motivational variables. They do not investigate, however, the individual levels of the mentioned constructs before the beginning of the studies. This research was conducted at the University of St. Gallen/Switzerland. The sample includes 695 first-year students who provided information about the individual level of the mentioned constructs. Descriptive statistics show that on average the students are highly motivated, have a high level of self-efficacy and are looking forward to their studies before their beginning. Yet, there are students who have a high level of fear of failure in the study in spite of their high motivation and self-efficacy. A logistic regression shows that there is a significant effect of fear of failure on the probability of study success. This paper shows that fear of failure can increase the probability of academic failure and thus become a self-fulfilling prophecy. It confirms fear as an important factor for academic success. Furthermore, other important factors for academic success, for example the high school grade, could be confirmed in this study
Keywords: Quantitative methods; Student learning; Emotion and Cognition; Social sciences; Higher education; Motivation and Emotion; Fear of Failure

A Multi-Theoretical Literature Review on Information Security Investments using the Resource-Based View and the Organizational Learning Theory - Weishäupl, Eva; Yasasin, Emrah; Schryen, Guido (International Conference on Information Systems)
The protection of information technology (IT) has become and is predicted to remain a key economic challenge for organizations. While research on IT security investment is fast growing, it lacks a theoretical basis for structuring research, explaining economic-technological phenomena and guide future research. We address this shortcoming by suggesting a new theoretical model emerging from a multi-theoretical perspective adopt-ing the Resource-Based View and the Organizational Learning Theory. The joint appli-cation of these theories allows to conceptualize in one theoretical model the organiza-tional learning effects that occur when the protection of organizational resources through IT security countermeasures develops over time. We use this model of IT security invest-ments to synthesize findings of a large body of literature and to derive research gaps. We also discuss managerial implications of (closing) these gaps by providing practical ex-amples.
Keywords: Information Security; Investment; Literature review; Resource-based View; Organi-zational Learning Theory; Multi-theoretical Perspective

Autonomous Learning of Representations - Walter, Oliver; Haeb-Umbach, Reinhold; Mokbel, Bassam; Paassen, Benjamin; Hammer, Barbara (KI - Kuenstliche Intelligenz)
Besides the core learning algorithm itself, one major question in machine learning is how to best encode given training data such that the learning technology can efficiently learn based thereon and generalize to novel data. While classical approaches often rely on a hand coded data representation, the topic of autonomous representation or feature learning plays a major role in modern learning architectures. The goal of this contribution is to give an overview about different principles of autonomous feature learning, and to exemplify two principles based on two recent examples: autonomous metric learning for sequences, and autonomous learning of a deep representation for spoken language, respectively.
Keywords: Representation learning; Metric learning; Deep representation; Spoken language

Zum Einfluss des didaktischen Designs auf das (motivationale) Erleben von Lehrveranstaltungen: Eine quantitative Fallstudie im Rahmen der Methodeneinführung in den Bildungswissenschaften - Goller, Michael (die hochschullehre)
Im Sinne eines Scholarship of Teaching and Learning wird in diesem Aufsatz die Neugestaltung einer eigenständig durchgeführten Lehrveranstaltung im Bereich der Forschungsmethoden empirisch untersucht. Die neugestaltete Lehrveranstaltung integriert sowohl direkt-instruktionale als auch kooperativ-offene Sitzungsformate und wird mit einer thematisch ähnlichen Lehrveranstaltung des Jahres 2012 verglichen, welche fast ausschließlich im Vorlesungsstil (direkt-instruktional) gehalten wurde. Im Mittelpunkt des Evaluationsvorhabens standen folgende Forschungsfragen: (1) Unterscheiden sich die summativen Evaluationen der Lehrveranstaltungen der Jahre 2012 und 2014 in den Variablen subjektiver Lernerfolg, Motivation zur selbstständigen Auseinandersetzung mit den Inhalten sowie Gesamteindruck des Seminars?, (2) Welchen Einfluss hat die Form der Sitzungsgestaltung (direkt-instruktional vs. kooperativ-offen) auf das Erleben von Kompetenz, Autonomie und sozialer Eingebundenheit?, (3) Welche Form der Sitzungsgestaltung wird von den Studierenden stärker akzeptiert? und (4) Welchen Einfluss hat die Form der Sitzungsgestaltung auf den subjektiven Lernerfolg der Studierenden? Empirisch zeigte sich, dass die neugestaltete Lehrveranstaltung des Jahres 2014 von den Studierenden in fast allen Variablen als lernwirksamer eingeschätzt wurde. Des Weiteren ergaben sich Hinweise, dass sich kooperativ-offene Sitzungsformate positiv auf motivationale Ausgangsbedingungen auswirken.
Keywords: Direkte Instruktion; Evaluation; Kooperatives Lernen; Methodenausbildung; Paderborn; Scholarship of Teaching and Learning

Alignment to the Actions of a Robot - Vollmer, Anna-Lisa; Rohlfing, Katharina; Wrede, Britta; Cangelosi, Angelo (International Journal of Social Robotics)
Alignment is a phenomenon observed in human conversation: Dialog partners' behavior converges in many respects. Such alignment has been proposed to be automatic and the basis for communicating successfully. Recent research on human-computer dialog promotes a mediated communicative design account of alignment according to which the extent of alignment is influenced by interlocutors' beliefs about each other. Our work aims at adding to these findings in two ways. (a) Our work investigates alignment of manual actions, instead of lexical choice. (b) Participants interact with the iCub humanoid robot, instead of an artificial computer dialog system. Our results confirm that alignment also takes place in the domain of actions. We were not able to replicate the results of the original study in general in this setting, but in accordance with its findings, participants with a high questionnaire score for emotional stability and participants who are familiar with robots align their actions more to a robot they believe to be basic than to one they believe to be advanced. Regarding alignment over the course of an interaction, the extent of alignment seems to remain constant, when participants believe the robot to be advanced, but it increases over time, when participants believe the robot to be a basic version.
Keywords: learning; Human-robot interaction; Alignment; Robot social; Action understanding

On the assessment of attitudes towards studying—development and validation of a questionnaire - Brahm, Taiga; Jenert, Tobias (Learning and individual differences : journal of psychology and education)
This research aims to develop and validate an instrument for the assessment of attitudes towards two particular objects: the Higher Education Institution (HEI) and the process of studying. Investigating attitudes towards studying at a HEI in a comprehensive way addresses an important research gap. It connects students' perception of the institution with teaching and learning. To validate the Assessment of Students' Attitudes towards Studying (ASAtS) Questionnaire, data was gathered at three different universities in Switzerland (820 students), Sweden (167) and Germany (133). Overall, the results show the internal consistency of the ASAtS. Its nomological validity is also supported by correlations with other constructs, such as intrinsic motivation and study performance. The ASAtS contributes to the theory on students learning by broadening the scope of research beyond learning in a narrow sense. From a practical point of view, it provides a tool for HE management to monitor students' perception of their HEI.
Keywords: Attitude; Student learning; Higher Education Institution; university; student experience

Augmented reality in informal learning environments: A field experiment in a mathematics exhibition - Sommerauer, Peter; Müller, Oliver (Computers and Education)
Keywords: Augmented reality; Cognitive theory of multimedia learning; Field experiment; Informal learning; Museum

Tutoring in adult-child-interaction: On the loop of the tutor's action modification and the recipient's gaze - Pitsch, Karola; Vollmer, Anna-Lisa; Rohlfing, Katharina; Fritsch, Jannik; Wrede, Britta (Interaction Studies)
Research of tutoring in parent-infant interaction has shown that tutors - when presenting some action - modify both their verbal and manual performance for the learner (‘motherese’, ‘motionese’). Investigating the sources and effects of the tutors’ action modifications, we suggest an interactional account of ‘motionese’. Using video-data from a semi-experimental study in which parents taught their 8 to 11 month old infants how to nest a set of differently sized cups, we found that the tutors’ action modifications (in particular: high arches) functioned as an orienting device to guide the infant’s visual attention (gaze). Action modification and the recipient’s gaze can be seen to have a reciprocal sequential relationship and to constitute a constant loop of mutual adjustments. Implications are discussed for developmental research and for robotic ‘Social Learning’. We argue that a robot system could use on-line feedback strategies (e.g. gaze) to pro-actively shape a tutor’s action presentation as it emerges.
Keywords: conversation analysis; interactional coordination; adult-child-interaction; feedback; gaze; quantification; social learning; motionese; tutoring

Herausforderungen der Kompetenzorientierung in der Studienprogrammentwicklung - Brahm, Taiga; Jenert, Tobias (Zeitschrift für Hochschulentwicklung)
Kompetenzorientierung ist ein wichtiges aktuelles Ziel bei der Studienprogrammentwicklung. Allerdings ist die Umsetzung in der Praxis mit zwei wesentlichen Herausforderungen verbunden: So ist zum einen der Wechsel von disziplinären Inhalten hin zu Kompetenzen wenig intuitiv; zum anderen wird die Formulierung so genannter Learning Outcomes als administrative Übung betrachtet. An der Universität St. Gallen wurde ein systematischer Prozess für die Qualitätsentwicklung der Studienprogramme eingeführt. Im Beitrag wird dieser Prozess im Hinblick auf die Kompetenzorientierung reflektiert. Es erscheint wesentlich, den Programmen möglichst viel Freiraum auf ihrem Weg zur Kompetenzorientierung zu überlassen und sie auf diese Weise zu unterstützen.
Keywords: Kompetenzorientierung; Studienprogrammentwicklung; Hochschulentwicklung; Hochschule; Learning Outcomes

On the assessment of attitudes towards the study process and the university: Attitudes towards the Study Environment Questionnaire (ASEQ) - Brahm, Taiga; Jenert, Tobias; Euler, Dieter
The purpose of the research was to develop and validate an instrument for the assessment of attitudes towards the study environment in higher education contexts. The questionnaire is designed to measure students' attitudes towards two particular objects: the university (or Higher Education Institution) and the process of studying. Five studies at two different universities were conducted to develop and validate the Attitudes towards the Study Environment Questionnaire (ASEQ). In total, 1640 students filled in the questionnaire. Reliability tests and exploratory factor analysis as well as confirmatory factor analysis showed satisfactory psychometric characteristics of the ASEQ. Each part of the questionnaire is internally consistent and construct validity of the scales is supported by correlations with other constructs as assumed by current theories: Positive attitudinal constructs (normative behavior, autonomy, joy, self-efficacy, and task value) are positively related to intrinsic motivation and the expected study performance while anxiety is negatively related to these constructs. Since attitudes towards the study situation are connected to student engagement and motivation, the study contributes to the theory of student learning by providing a validated instrument to assess attitudes. Thus, the ASEQ can support further research on student performance and development by providing an instrument for the hitherto neglected but nonetheless extremely relevant domain of attitudes. Also, the questionnaire can be used as a diagnostic instrument for higher education faculty and administration to trace students' attitudinal development over time - a factor of prime importance for student socialization during the introductory phase of studying.
Keywords: attitudes; teaching and learning; studying; higher education institution; theory of planned behavior; instrument development

Educating attention: recruiting, maintaining, and framing eye contact in early natural mother-infant interactions - Nomikou, Iris; Rohlfing, Katharina; Szufnarowska, Joanna (Interaction Studies)
In a longitudinal naturalistic study, we observed German mothers interacting with their infants when they were 3 and 6 months old. Pursuing the idea that infants’ attention is socialized in everyday interactions, we explored whether eye contact is reinforced selectively by behavioral modification in the input provided to infants. Applying a microanalytical approach focusing on the sequential organization of interaction, we explored how the mother draws the infant’s attention to herself and how she tries to maintain attention when the infant is looking at her. Results showed that eye contact is reinforced by specific infant-directed practices: interrogatives and conversational openings, multimodal stimulation, repetition, and imitation. In addition, these practices are contingent on the infant’s own behavior. By comparing the two data points (3 and 6 months), we showed how the education of attention evolves hand-in-hand with the developing capacities of the infant.
Keywords: interactional adaptation; multimodal input; social learning; ecology of attention; eye contact

Optimierung des einsatzbezogenen Lernens durch Wissensidentifikation - Pottebaum, Jens
Keywords: Arbeitsorganisation; E-Learning; Lernorganisation; Lerntechnik; Wissensmanagement

Didaktische Potenziale des Mobile Learning für die Berufsbildung: Erfahrungen aus einem Pilotprojekt am Center for Young Professionals in Banking in der Schweiz - Seufert, Sabine; Jenert, Tobias; Kuhn-Senn, Andrea (Berufsbildung in Wissenschaft und Praxis)
Mobile Learning liegt in der beruflichen Bildung seit dem Aufkommen von Smartphones, Tablet-PCs1 und speziell entwickelten Applikationen (Mobile Apps) im Trend. Ziel des Beitrags ist es, die didaktischen Potenziale des Mobile Learning durch den Einsatz von Tablet-PCs in der beruflichen Ausbildung zu untersuchen. Als Ausgangspunkt dient dabei das Fallbeispiel des Center for Young Professionals in Banking in der Schweiz, das im Jahr 2011 eine umfassende Pilotstudie durchgeführt hat. Ausgehend vom konkreten Fall werden anschliessend die Potenziale für medienbezogene Kompetenzen sowie eine "didaktische Landkarte" zur Verortung von Mobile-Learning-Szenarien eingeführt, um die verschiedenen pädagogischen Leitvorstellungen dieser Szenarien aufzuzeigen.
Keywords: mobile learning; tablets; tablet learning; mobile technologies; elearning; TEL

How to Assess and Study the Cultural Dimension of Social Interactions in Higher Education Institutions (HEI) - Gebhardt, Anja; Jenert, Tobias
Keywords: learning culture; social interaction

Algorithm Selection Based on Exploratory Landscape Analysis and Cost-Sensitive Learning - Bischl, Bernd; Mersmann, Olaf; Trautmann, Heike; Preuß, Mike (Proceedings of the 14th Annual Conference on Genetic and Evolutionary Computation)
The steady supply of new optimization methods makes the algorithm selection problem (ASP) an increasingly pressing and challenging task, specially for real-world black-box optimization problems. The introduced approach considers the ASP as a cost-sensitive classification task which is based on Exploratory Landscape Analysis. Low-level features gathered by systematic sampling of the function on the feasible set are used to predict a well-performing algorithm out of a given portfolio. Example-specific label costs are defined by the expected runtime of each candidate algorithm. We use one-sided support vector regression to solve this learning problem. The approach is illustrated by means of the optimization problems and algorithms of the BBOB’09/10 workshop.
Keywords: machine learning; exploratory landscape analysis; fitness landscape; benchmarking; evolutionary optimization; bbob test set; algorithm selection

Weblogs zur Unterstützung der Theorie-Praxis-Integration in der Wirtschaftslehrenden-Ausbildung - Jenert, Tobias; Gebhardt, Anja; Käser, Reto (Zeitschrift für E-Learning)
Eine zentrale Herausforderung in der Ausbildung angehender Wirtschaftslehrpersonen stellt die sinnvolle Verknüpfung von Theorie- und Praxiserfahrungen dar. Im Rahmen der Ausbildung angehender Wirtschaftslehrpersonen an der Universität St. Gallen wird eine Lernumgebung gestaltet, die eine Verschränkung von Theorie- und Praxiserfahrungen ermöglichen soll. Die Lernprozesse der Studierenden werden dabei durch didaktisch angeleitete Weblogarbeit unterstützt. Trotz der Lernchancen, die sich aus einer Verknüpfung von theoretischen und praktischen Lernphasen ergeben, schätzen die Studierenden den Nutzen der Weblogarbeit als äusserst gering ein. Die Studierenden bei der reflexiven Integration praxisnaher und theoretischer Lernerfahrungen zu unterstützen, ist eine Herausforderung, die dezidierter Anleitung und Förderung durch die Lehrpersonen bedarf
Keywords: Weblog; Blog; e-learning; TEL; higher education; business education

Prior entry explains order reversals in the attentional blink. - Olivers, Christian N. L.; Hilkenmeier, Frederic; Scharlau, Ingrid (Attention, Perception, & Psychophysics)
When two targets are presented in rapid succession, the first target (T1) is usually identified, but the second target (T2) is often missed. A remarkable exception to this 'attentional blink' occurs when T2 immediately follows the first T1, at lag 1. It is then often spared but reported in the wrong order—that is, before T1. These order reversals have led to the hypothesis that 'lag 1 sparing' occurs because the two targets merge into a single episodic representation. Here, we report evidence consistent with an alternative theory: T2 receives more attention than T1, leading to prior entry into working memory. Two experiments showed that the more T2 performance exceeded that for T1, the more order reversals were made. Furthermore, precuing T1 led to a shift in performance benefits from T2 to T1 and to an equivalent reduction in order reversals. We conclude that it is not necessary to assume episodic integration to explain lag 1 sparing or the accompanying order reversals. (PsycINFO Dat
Keywords: attentional blink; order reversals; prior entry; working memory; visual attention; attentional performance; Adolescent; Adult; Attention; Attentional Blink; Color Perception; Cues; Discrimination (Psychology); Female; Humans; Male; Memory; Short-Term; Pattern Recognition; Visual; Psychophysics; Reaction Time; Reversal Learning; Sensory Gating; Serial Learning; Young Adult; Eyeblink Reflex; Stimulus Change; Stimulus Parameters; Visual Attention; Attentional Blink; Short Term Memory

Language Does Something: Body Action and Language in Maternal Input to Three-Month-Olds - Nomikou, Iris; Rohlfing, Katharina (IEEE Transactions on Autonomous Mental Development)
Keywords: acoustic packaging; mother-child interaction; social learning; multimodal grounding in input; ecology of interactions; synchrony

Zugänge zum Begriff der Lernkultur: Eine Systematisierung auf Basis kultur-und lerntheoretischer Überlegungen - Jenert, Tobias; Gebhardt, Anja
"Lernkultur" wird als Begriff häufig gebraucht und fast ebenso häufig definiert  das gilt für den betrieblichen Kontext ebenso wie für die Bereiche der Schul-, Hochschul-, Berufs- und Erwachsenenbildung (z. B. Wulf, Althans, Blaschke, Ferrin, Göhlich, Jörissen, Mattig et al., 2007; Jenert, Zellweger Moser, Dommen & Gebhardt, 2009; Kirchhöfer, 2004; Erpenbeck & Sauer, 2000). Trotz der grossen Aufmerksamkeit, die der Begriff in den letzten zwei Jahrzehnten erfahren hat, kann man nicht von einem in sich geschlossenen Forschungsprogramm sprechen. Die Zugänge zum Phänomenbereich Lernkultur sind ebenso vielfältig wie die hinter einzelnen Ansätzen stehenden Lernkulturkonstrukte. Den Autoren ist keine Publikation bekannt, welche unterschiedliche Ansätze der Lernkulturforschung systematisch aufarbeitet. Eine wichtige Referenzquelle ist der Bericht von Kuh und Whitt (1988) "The Invisible Tapestry: Culture in American Colleges and Universities". Ausgehend von einer fundierten Übersicht zu unterschiedlichen Zugängen zum Kulturbegriff (oft in starker Anlehnung an die Organisationskulturforschung (vgl. Allaire & Firsirotu, 1984)) stellen die Autoren ein Rahmenmodell zur Analyse von Hochschulkulturen vor (Kuh und Whitt, 1988, S. 56). Diese Arbeit erweist sich für ein besseres Verständnis unter-schiedlicher Zugänge zum Lernkulturbegriff als aufschlussreich, weil im Kontext Hoch-schule zwangsweise viele Aspekte des Lernens und Lehrens angesprochen werden. Allerdings fokussiert auch dieser Bericht nicht das Konstrukt der Lernkultur und bietet damit nur einen Ausgangspunkt für die Identifizierung unterschiedlicher Zugänge.
Keywords: Lernkultur; learning culture; culture theory; approaches to learning culture; culture of learning

Developing feedback: How children of different age contribute to a tutoring interaction with adults - Vollmer, Anna-Lisa; Pitsch, Karola; Lohan, Katrin Solveig; Fritsch, Jannik; Rohlfing, Katharina; Wrede, Britta (Development and Learning (ICDL), 2010 IEEE 9th International Conference on Development and Learning)
Keywords: tutoring interaction; social interaction; video signal processing; robot systems; paediatrics; neurophysiology; Learning; infant; feedback; biology computing; cognitive capabilities; cognition; children

Lernkulturen an Hochschulen: Theoretische Überlegungen zur Betrachtung studentischen Lernens unter individueller, pädagogischer und organisationaler Perspektive - Jenert, Tobias; Zellweger, Franziska; Dommen, Jenny; Gebhardt, Anja
Keywords: Lernkultur; Hochschule; HEI; learning culture; higher education; teaching and learning; Hochschullehre

Security in Large-Scale Internet Elections: A Retrospective Analysis of Elections in Estonia, The Netherlands, and Switzerland - Schryen, Guido; Rich, Eliot (IEEE Transactions on Information Forensics & Security)
Remote voting through the Internet provides convenience and access to the electorate. At the same time, the security concerns facing any distributed application are magnified when the task is so crucial to democratic society. In addition, some of the electoral process loses transparency when it is encapsulated in information technology. In this paper, we examine the public record of three recent elections that used Internet voting. Our specific goal is to identify any potential flaws that security experts would recognize, but may have not been identified in the rush to implement technology. To do this, we present a multiple exploratory case study, looking at elections conducted between 2006 and 2007 in Estonia, Netherlands, and Switzerland. These elections were selected as particularly interesting and accessible, and each presents its own technical and security challenges. The electoral environment, technical design and process for each election are described, including reconstruction of details which are implied but not specified within the source material. We found that all three elections warrant significant concern about voter security, verifiability, and transparency. Usability, our fourth area of focus, seems to have been well-addressed in these elections. While our analysis is based on public documents and previously published reports, and therefore lacking access to any confidential materials held by electoral officials, this comparative analysis provides interesting insight and consistent questions across all these cases. Effective review of Internet voting requires an aggressive stance towards identifying potential security and operational flaws, and we encourage the use of third party reviews with critical technology skills during design, programming, and voting to reduce the changes of failure or fraud that would undermine public confidence.
Keywords: e-voting; Internet voting; Internet election; security; verifiability; RIES; Estonia; Neuchâtel

People modify their tutoring behavior in robot-directed interaction for action learning - Vollmer, Anna-Lisa; Lohan, Katrin Solveig; Fischer, Kerstin; Nagai, Yukie; Pitsch, Karola; Fritsch, Jannik; Rohlfing, Katharina; Wrede, Britta (Development and Learning, 2009. ICDL 2009. IEEE 8th International Conference on Development and Learning)
In developmental research, tutoring behavior has been identified as scaffolding infants' learning processes. It has been defined in terms of child-directed speech (Motherese), child-directed motion (Motionese), and contingency. In the field of developmental robotics, research often assumes that in human-robot interaction (HRI), robots are treated similar to infants, because their immature cognitive capabilities benefit from this behavior. However, according to our knowledge, it has barely been studied whether this is true and how exactly humans alter their behavior towards a robotic interaction partner. In this paper, we present results concerning the acceptance of a robotic agent in a social learning scenario obtained via comparison to adults and 8-11 months old infants in equal conditions. These results constitute an important empirical basis for making use of tutoring behavior in social robotics. In our study, we performed a detailed multimodal analysis of HRI in a tutoring situation using the example of a robot simulation equipped with a bottom-up saliency-based attention model. Our results reveal significant differences in hand movement velocity, motion pauses, range of motion, and eye gaze suggesting that for example adults decrease their hand movement velocity in an Adult-Child Interaction (ACI), opposed to an Adult-Adult Interaction (AAI) and this decrease is even higher in the Adult-Robot Interaction (ARI). We also found important differences between ACI and ARI in how the behavior is modified over time as the interaction unfolds. These findings indicate the necessity of integrating top-down feedback structures into a bottom-up system for robots to be fully accepted as interaction partners.
Keywords: robot simulation; hand movement velocity; robotic interaction partner; robotic agent; robot-directed interaction; multimodal analysis; Motionese; Motherese; intelligent tutoring systems; immature cognitive capability; human computer interaction; eye gaze; child-directed speech; child-directed motion; bottom-up system; bottom-up saliency-based attention model; adult-robot interaction; adult-child interaction; adult-adult interaction; human-robot interaction; action learning; social learning scenario; social robotics; software agents; top-down feedback structures; tutoring behavior